Community-Based Male Engagement for Maternal Health: The SAPA SUAMI Initiative in Central Kalimantan - Putri Oktariani Valentina; Ina Indrayanti; Rabia Wahdah; Susanti Suhartati (HM Publisher, 2026)
Husband involvement in maternal health remains a critical challenge in low- and middle-income countries, contributing to suboptimal antenatal care utilization. This study evaluated the effectiveness of the SAPA SUAMI (Sayangi dan Pahami Suami — Love and understand the role of husbands) community empowerment program in enhancing husband knowledge and support for reproductive health service access among pregnant women in Palangka Raya City, Central Kalimantan, Indonesia, aligning with Sustainable Development Goal 3 (Good Health and Well-Being) and SDG 5 (Gender Equality). A pre-experimental study with one-group pre-test and post-test design involved 20 couples (pregnant women and their husbands) at UPTD Puskesmas Panarung on 17 February 2026. The intervention comprised structured health education, interactive group discussion, and educational leaflet distribution focusing on the husband's role in antenatal care support. Knowledge was assessed using a 10-item questionnaire. Mean knowledge scores improved significantly from 8.70 (standard deviation 1.63) to 9.85 (standard deviation 0.37) post-intervention, representing an 11.5% increase (Wilcoxon signed-rank test: Z = -2.449, p = 0.014; effect size r = 0.55). The proportion of participants achieving maximum scores increased from 70.0% to 85.0%, while participants scoring below 8 decreased from 20.0% to 0.0%. In conclusion, these preliminary findings suggest that the SAPA SUAMI program effectively enhanced husband awareness regarding their supportive role in maternal health care, contributing to community empowerment for improved antenatal care access and advancing SDG 3 and SDG 5 targets in a primary health care setting. Multi-site replication with behavioral outcomes and delayed follow-up is recommended.